2016
DOI: 10.1111/cea.12692
|View full text |Cite
|
Sign up to set email alerts
|

Lack of allergy to timothy grass pollen is not a passive phenomenon but associated with the allergen‐specific modulation of immune reactivity

Abstract: Background Timothy grass (TG) pollen is a common seasonal airborne allergen associated with symptoms ranging from mild rhinitis to severe asthma. Objective The aim of this study was to characterize changes in TG-specific T cell responses as a function of seasonality. Methods Peripheral blood mononuclear cells (PBMC) obtained from allergic individuals and non-allergic controls, either during the pollen season or out-of-season, were stimulated either with TG extract or a pool of previously identified immunod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 63 publications
4
43
0
Order By: Relevance
“…Specific immunotherapy (SIT) has been shown to induce durable immunological changes in response to the allergen, through generating neutralizing antibodies, through suppressing numbers and activity of allergen‐specific Th2 cells and type 2 innate lymphoid cells (ILC2s), and by inducing regulatory T‐cell activity 2. Successful SIT has been associated with enhanced release of IL‐10 in PBMC cultures restimulated with allergen,3 serum‐dependent suppression of cross‐presentation by B cells,4 and selective loss of those T‐cell clones with allergen‐epitope specificities that are increased in atopic individuals compared to healthy controls 5, 6. Specific immunotherapy (SIT) induces long‐term tolerance to the allergen, as evidenced by the absence of allergic manifestations upon repeated allergen challenges 1…”
Section: Introductionmentioning
confidence: 99%
“…Specific immunotherapy (SIT) has been shown to induce durable immunological changes in response to the allergen, through generating neutralizing antibodies, through suppressing numbers and activity of allergen‐specific Th2 cells and type 2 innate lymphoid cells (ILC2s), and by inducing regulatory T‐cell activity 2. Successful SIT has been associated with enhanced release of IL‐10 in PBMC cultures restimulated with allergen,3 serum‐dependent suppression of cross‐presentation by B cells,4 and selective loss of those T‐cell clones with allergen‐epitope specificities that are increased in atopic individuals compared to healthy controls 5, 6. Specific immunotherapy (SIT) induces long‐term tolerance to the allergen, as evidenced by the absence of allergic manifestations upon repeated allergen challenges 1…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies on differences between immune recognition and responses of non-sensitized and sensitized donors in the JC system are extremely rare. Several reports suggest that non-sensitized individuals mount an immune response distinct from those of allergic individuals and are not oblivious to antigen stimulation 2527 . Thus defining the features and targets of healthy individuals is important and understudied, and could provide insights for the development of safer and more efficacious immunotherapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, focused on Mugwort allergy, reported an ex vivo frequency of peptide-specific T cells of 0-0.029% in allergic cohort [34]. In a third study, performed with cells from patients allergic to Timothy grass, the authors reported epitope-specific T cell frequencies of 0.6-0.75% of the total CD4+ T cell subset [35], with a modest increase in frequencies detected during grass pollen season. The rarity of allergen-specific T cells poses a great challenge for epitope identification, as it will require the T cell reactivity assay to reliably detect a few single cells that respond to the peptide among several thousands of CD4+ T cells.…”
Section: Allergen-specific T Cell Frequenciesmentioning
confidence: 98%
“…In vaccinology, tetramers are often used to track frequencies of peptide-specific T cells in the blood before and after vaccination or boost. Similarly, in allergy, tetramers have been used to quantify numbers of specific T cells as a variable of allergen season [35], allergen-specific immunotherapy [39], and disease status [34,40]. In addition, tetramer staining can be combined with other methodologies to perform more detailed immunological characterization of allergen-specific T cells.…”
Section: Mhc Tetramer Assaymentioning
confidence: 99%
See 1 more Smart Citation